Coordinated spectral and XRD analyses of magnesite‐nontronite‐forsterite mixtures and implications for carbonates on Mars. Issue 4 (8th April 2013) - Bishop, Janice L.; Perry, Kaysea A.; Darby Dyar, M.; Bristow, Thomas F.; Blake, David F.; Brown, Adrian J.; Peel, Samantha E.
Abstract : [1] Mineral detection on Mars largely relies on laboratory data of minerals and mineral mixtures. The objective of this study is to provide reflectance spectra in the visible/near‐infrared (VNIR) and mid‐IR regions, X‐ray diffraction (XRD) data and Mössbauer spectra of a suite of carbonate, phyllosilicate and olivine mixtures in order to facilitate identification and characterization of these minerals on Mars. Remote sensing observations indicate that combinations of these minerals are present in ancient rocks on Mars around the Isidis Basin and in Gusev crater. Magnesite, nontronite, and forsterite size fractions <125 µm were selected for this study. Results of the VNIR reflectance analyses illustrate the complexity of VNIR spectra of mixtures. Analyses of the NIR band depths near 2.3, 2.5, 3.4, and 4 µm showed clear trends with carbonate abundance, although the data are not linear. Mixtures of magnesite and nontronite exhibited a band near 2.3 µm much closer to that observed for nontronite than that for magnesite. VNIR analyses of the mixtures indicated that a small amount of forsterite in any of the mixtures contributed a large increase in the broad ~1 µm band and, hence, the red slope characteristic of Fe 2+ ‐bearing minerals. Mid‐IR mixture spectra were dominated by magnesite and forsterite, and nontronite was much more difficult to detect by mid‐IR spectra in the mixtures. This could be related to why phyllosilicates are detected in many locations on Mars using data collected by the Compact Reconnaissance Imaging Spectrometer for Mars, but not detected using data collected by the Thermal Emission Spectrometer. Mössbauer spectroscopy is well suited for analyses of Fe 2+ ‐ and Fe 3+ ‐bearing minerals, and modeling of the peak areas gave well‐correlated trends for nontronite and forsterite abundances where abundant Fe was present. XRD full‐pattern fitting analyses were performed on the magnesite‐forsterite series, giving results within 6 wt % of the actual values, with a mean difference between actual and calculated values of 2.4 wt %. This study provides important laboratory data for characterizing the spectral and XRD properties of mineral mixtures that will facilitate mineral identification on Mars. Carbonates, in particular, have been primarily observed at low abundances and in small outcrops, and they are frequently found mixed with other minerals. Through analyses of mineral mixtures using multiple data sets, this study seeks to provide ground truthing that will enable better coordination of carbonate detections in the dust and rocks of Mars. Key Points: This study provides ground truthing for carbonate identification on Mars Carbonate detections in mixtures on Mars should be successful using CheMin carbonates and Fe, Mg‐clays could be difficult to detect at 2.3 um using CRISM